Kontroversi Surat Al-Fatihah Dalam Pandangan Arthur Jeffery - Dhulkifli, Muhammad Luthfi (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2019)
AbstractAmongst some orientalist of Qur’anic studies, Arthur Jeffery was one of the controversial figures for the idea of a critical edition of the Qur’an. For Jeffery, the Qur’an existed today is unreasonable and its arrangement is clearly haphazard. One of his critical argument is surah al-Fatihah which indicated not originally part of the Qur’an. His work “the variant readings of the Fatihah” showed some peculiar nature of al-Fatiha with the evidence of two Fatihah different versions. Jeffery’s variants study is a polemical argument as its contradicts to the Muslim scholar arguments. For Muslim scholars, al-Fatihah is an integrated part of Qur’an. Therefore, this article will analyze Jeffery’s argument on al-Fatihah through a descriptive-analytic method. Based on historical, language, and qira’ah study, Jeffery’s argument is incorrect. In addition, Jeffery failed to show the existence of his evidence of variant of al-Fatihah.Keywords: Critic; Controversy; Fatiha; Muslim; the Qur’an  AbstrakDiantara sekian banyak para orientalis pengkaji al-Qur’an, Arthur Jeffery merupakan salah satu sosok yang paling kontroversial dengan gagasannya untuk membuat al-Qur’an edisi kritis. Menurut Jeffery, al-Qur’an yang ada saat ini sangat tidak jelas dan susunannya dilakukan secara sembarangan. Salah satu bagian yang Jeffery kritisi adalah surat al-Fatihah yang dianggap bukan bagian dari al-Qur’an. Dalam tulisannya yang berjudul the variant readings of the Fatihah, dia menunjukkan kejanggalan dalam surat al-Fatihah dengan menunjukkan bukti dua variasi surat al-Fatihah yang berbeda. Kajian ini mengundang polemik karena bertentangan dengan pandangan para sarjana Muslim yang menganggap al-Fatihah sebagai bagian penting dari al-Qur’an. Tulisan ini akan menganalisasi pandangan Jeffery terhadap surat al-Fatihah melalui metode deskriptif-analitis. Melalui kajian historis, kebahasaan, dan ilmu qira’at, argumen skeptis Jeffery terhadap al-Fatihah terbantahkan. Ditambah lagi, Jeffery tidak mampu membuktikan keberadaan variasi surat al-Fatihah yang dia yakini.  Kata Kunci: al-Fatihah; al-Qur’an; Kontroversi; Kritik; Muslim